Green solar dehydrator / A. N. Alias ... [et al.] - Alias, A. N.; Khalid, M. H.; Sahapini, N. F. M.; Mahfodz, Z.; Abdullah, F.; Julius, R.; Yahya, M. A.; Fariesha, F. (2015)
A solar drying system with portable design which consisting of different numbers of layer coated with aluminium foil was produced. This study was about using direct solar energy to dry food. From the information gathered from literature study, the prototype of several portable solar dehydrators with different number of layer coated with aluminium foil and the normal drying system was constructed and used in this experimental drying test. A portable solar dehydrator helps the food to dry faster and allow food to be better in quality. The earlier parameter for this solar dehydrator was the weight and followed with the percentage of the water loss. This portable solar dehydrator also can be used to dry the fruits. One major benefit of this dehydrator is its construction or design. It was simple constructed and was made with low cost materials. For all test conditions, the materials were dried with system efficiency of 60% to 78%.